The Next Frontiers in Stroke Prevention: Optimizing Left Atrial Appendage Closure in Atrial Fibrillation: Current Devices, Imaging-Guided Strategies, and Emerging Approaches - Zain Al-Abdeen Mohammed Qassim; Mohamedanas Mohamedfaruk Patni; Biji Thomas George; Subhranshu Sekhar Kar; Rajani Dube; Reema Mohammed Saeed Al Shaibani; Ghina Hasan Yassin; Yara Mamoun Theyabat; Ibrahim Alabid; Malak Mohammed Qassim (Journal of Clinical Medicine, 2026)
Background/Objectives: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is associated with ischemic stroke, systemic thromboembolism, heart failure, and mortality. Although oral anticoagulation (OAC) remains the cornerstone of stroke prevention, long-term therapy may be limited by bleeding risk, contraindications, intolerance, nonadherence, or thromboembolic events despite treatment. Left atrial appendage closure (LAAC) has therefore emerged as a non-pharmacological alternative for selected patients with nonvalvular AF. This review aimed to synthesize current evidence on LAAC, focusing on comparative efficacy versus OAC, device evolution, imaging-guided strategies, antithrombotic management, procedural optimization, unresolved challenges, and emerging technologies. Methods: This state-of-the-art narrative review was informed by targeted, non-systematic searches of PubMed and Scopus for publications from January 2009 to June 2026. Evidence was selected purposively to represent clinically relevant guidelines, randomized trials, registries, comparative observational studies, systematic reviews, meta-analyses, imaging studies, device-comparison studies, and reports of emerging technologies. The selected evidence was synthesized narratively; no exhaustive screening process, PRISMA flow diagram, formal risk-of-bias assessment, or quantitative synthesis was performed. Results: Randomized evidence was context dependent. OPTION supported LAAC as an alternative to oral anticoagulation in selected anticoagulation-eligible patients undergoing atrial fibrillation ablation. CHAMPION-AF established noninferiority of Watchman FLX to non–vitamin K antagonist oral anticoagulants for its composite efficacy endpoint in a predominantly moderate-risk, anticoagulation-eligible population and demonstrated less non-procedural bleeding, although ischemic stroke occurred numerically more often after LAAC. In contrast, CLOSURE-AF did not establish noninferiority of LAAC to physician-directed medical therapy in an older population at high risks of both stroke and bleeding. These findings indicate that the comparative value of LAAC depends strongly on patient selection, comparator therapy, endpoint composition, procedural risk, and trial design. Observational, registry, and emerging evidence was considered supportive or hypothesis-generating rather than equivalent to randomized evidence. OPTION enrolled only patients undergoing or recently undergoing AF ablation who were suitable for anticoagulation. CHAMPION-AF included 3000 anticoagulation-eligible patients but had relatively low baseline bleeding risk, while CLOSURE-AF studied 912 substantially older, higher-risk patients and did not meet its noninferiority criterion. Conclusions: LAAC has evolved into a precision-guided intervention integrating patient risk, left atrial appendage anatomy, device choice, imaging, antithrombotic therapy, and structured surveillance. Further studies are needed to optimize patient selection, standardize post-procedural therapy, and clarify its long-term role compared with contemporary direct oral anticoagulant therapy.